Management of peripartum hysterectomies performed on patients with placenta percreta in a tertiary central hospital. (19th March 2019) - Sak, Sibel; Barut, Mert; Incebiyik, Adnan; Uyanikoglu, Hacer; Hilali, Nese; Sak, Muhammet
Abstract: Objective: The main objective of this study is to analyse the circumstances and management of peripartum hysterectomies performed on patients with placenta percreta. Methods: This study included 37 patients who were diagnosed with placenta percreta, a condition in which the placenta invades the uterine wall, and who therefore underwent a peripartum hysterectomy. Their demographic characteristics, history of past caesareans, uterine surgery and curettage, duration of hospitalization, admission to an intensive care unit, neonatal outcomes, skin and uterus incision type, hypogastric artery ligation (HAL), complications, quantities of transfused ES (erythrocyte suspensions), and FFP (fresh frozen plasma), maternal morbidity and mortality and postoperative pathology results were retrospectively reviewed. Results: All pregnant patients who underwent a caesarean hysterectomy due to placenta percreta had a history of caesarean section and also of placenta praevia totalis. Bilateral HAL was performed in two patients (5.4%), owing to uncontrollable bleeding during the bladder dissection. The complications most frequently observed were bladder injury (13.5%), followed by infection (8.1%) and relaparotomy (5.4%). There was no mortality. Twenty-three (62.2%) of the patients had ES and 11 patients (29.7%) had FFP transfusions. According to the histopathology findings, 33 of the 37 patients (89.1%) reportedly had placenta percreta, three patients had placenta increta, and one patient had placenta accreta. Analysis of the neonatal status at birth showed that the gestational age was, on average, the 35th week. The birth weight was normal in relation to the gestational week, but the first and fifth minute Apgar score, which measures the physical condition of an infant, was found to be lower than the normal range. Conclusions: If a pregnant patient undergoes uterine surgery or has a history of a caesarean with placenta praevia, she is likely to have placenta percreta. In placenta percreta cases with bladder invasion; careful suturing of the high-volume vessels on the posterior wall of the bladder, through the bladder serosa is important in reducing the amount of bleeding and preventing future fistula formation.